The regional blood transfusion centers project = (The World Bank in Vietnam (WB), 2003)
The Regional Blood Transfusion Centers (RBTCs) Project for Vietnam development objective is to secure the health benefits of safe blood transfusion for the population served by hospitals covered by the RBTCs; and the proposed closing date extension will provide the needed conditions to meet the PDO. The project will continue to aim at meeting the increasing demand for safe blood transfusions through funding the construction and equipment of RBTCs, to provide reliable blood services for the project covered areas and serve as models for future blood centers across the country. However, instead of financing construction of four RBTCs as envisaged at appraisal, it will finance the construction and equipment of three RBTCs. The recently built Blood Transfusion Center at the Ho Chi Minh City (HCMC) Hematology Hospital, together with the Cho Ray Hospital Blood Bank will provide blood services for HCMC as well as the neighboring provinces. Therefore the cancellation of the construction of HCMC RBTC will not adversely affect the supply of the blood transfusion services and blood products to the intended beneficiary population. This will also prevent possible duplication with the efforts that the local government is putting in place. At appraisal it was determined that benefits of large up front investments to improve blood safety will be maximized by expanding output in only those blood centers with the greatest potential of producing and utilizing the highest volume of safe blood services.